Landscape and geochemical features of the territory of the city of Vyzhnytsia, Chernivtsi oblast. - Prysakar, Vitalii; Khodan, Halyna; Dobynda, Iryna (Iasi, 2022)
25 A significant differentiation of landscape areas and tracts of the territory determines the diversity of its natural geochemical landscapes, which is enhanced by the anthropogenic and man-made load. The latter enhances the geochemical differentiation of geochemical parameters, mainly in places of man-made contact. The territory of Vyzhnytsia, which is located at the junction of two physical-geographical regions of the Carpathian physical-geographical country, has such characteristics. There is a direct collision of various landscapes. The city landscape combines the properties of the natural landscape and the functional features of urban man-made systems and is a hierarchical system consisting of interacting natural and technical subsystems that develop according to natural and social laws. Vyzhnytsia is located in the foothills of the Chernivtsi oblast, in the area of meadow-forest and mountain-forest types of landscapes. The valley landscapes of the Cheremosh and Vyzhenka rivers are widespread as well. According to geochemical zoning, the territory of the city of Vyzhnytsia belongs to the Cheremosh-Banyliv landscape-geochemical settlement district, which is, in general, a valley-terrace meadow-forest area with grey
Keywords: . Keywords: landscape, geochemical zoning, settlement landscape, natural landscape